Violência doméstica e familiar contra a mulher face à Lei Maria da Penha - Borgonhone, Eny Ribeiro (2008)
The vision of the person of the woman as inferior and unworthy of several rights, has always been pari passu with different treatment of gender, which often came (and reached) to acts of domestic violence against women and family, from this point of departure sought Up tackle domestic violence against women in their historical roots, cultural, social and legal, because, for a long time the inequality was institutionalised, supporting domestic violence, and the approach to contemporary issues such as wage differentiation, objetificação of women, the persistence of domestic violence as vestiges of unequal treatment, although equiparadoras laws, as the Federal Constitution of Brazil. The incidence of domestic violence in alarming proportions and condemnation of Brazil by the International Court of Human Rights led the drafting of a specific law to protect women in this type of violence, Law 11.340/06 - PML, which shows poor to contain the cases of domestic violence and family by the lack of physical infrastructure for effectiveness of its listed, and, above all, through the view that it is applied, that is, the vision of the formalistic approach, disregarding the historicity of the serious problem of domestic violence and family, as well as aspects relevant today, moving increasingly the law of reality material. With this, you reach the conclusion that the formal logic, guidance in the implementation of the PML-way silogística-dedutiva or mechanized way and not capable of performing their attempts, bearing in mind that the legal argumentative logic, can be an alternative to that PML to reach their goals to prevent and correct cases of domestic violence against women and family, because this perspective the law is applied by means of thought and reflected a decision based on all the remote environment and the current problem.